If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x = 4(-3x + 6) Reorder the terms: 3x = 4(6 + -3x) 3x = (6 * 4 + -3x * 4) 3x = (24 + -12x) Solving 3x = 24 + -12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12x' to each side of the equation. 3x + 12x = 24 + -12x + 12x Combine like terms: 3x + 12x = 15x 15x = 24 + -12x + 12x Combine like terms: -12x + 12x = 0 15x = 24 + 0 15x = 24 Divide each side by '15'. x = 1.6 Simplifying x = 1.6
| 3m=228 | | x+8=1+2x | | -32=r^5 | | -20=8+7b | | 20t+7=-6(4t-5)+2t+(5t+1)+x | | -8x+12+2x=-30 | | 4r=756 | | 6x+11=8x+34 | | 3x(2)+5x-17+6x+20= | | 2x(4)=8 | | 3n+2(n+8)=6 | | 2x+12=2x+2x | | 24-2(4p+8)=56 | | 9=1+1.4ln(x+1) | | ln(x+4)+ln(x-5)=2ln(x) | | ln(2x+1)=2 | | 2x+1(x)=105 | | 9p+4-p-20=56 | | 3r=42 | | 5x-9=3+-6x | | -3y+10=-5 | | 30x^2-19x-63=0 | | 1.1+ln*x^2=6 | | x+4.23=8.2 | | 6x-7=-15-2x | | 3w+8+2w=13 | | 36=3(b+3)+9 | | 6+2m+3=15 | | 1-2x+3=-2x-2 | | 41=6x+5x+8 | | 3y+2x+3xy-2y= | | 77d-3+2d=5d-8+1 |